1982
DOI: 10.1002/ar.1092020106
|View full text |Cite
|
Sign up to set email alerts
|

The histology and fine structure of glands in the rat respiratory tract

Abstract: The structure of rat respiratory glands has been investigated by light and electron microscopy. The glands exhibited a tubulo-acinar organization. Individual secretory units were composed of serous tubules or serous demilunes and mucous tubules with narrow lumens at the blind end (proximally), and of mucous ducts with wide lumens which opened to the tracheal lumen distally. Near the junction of the duct with the trachea, mitochondria-rich cells and a few ciliated cells were interspersed with mucous cells. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…Histology of the lower respiratory system in other rodents such as the laboratory rat (Spicer et al, 1982;Choi et al, 2000;Widdicombe et al, 2001), hamster (Kennedy et al, 1978), squirrel (Nakakuki, 1979) and guinea pig (Kliment et al, 1972) have been described in detail. However, such description in the African Giant pouched rat is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Histology of the lower respiratory system in other rodents such as the laboratory rat (Spicer et al, 1982;Choi et al, 2000;Widdicombe et al, 2001), hamster (Kennedy et al, 1978), squirrel (Nakakuki, 1979) and guinea pig (Kliment et al, 1972) have been described in detail. However, such description in the African Giant pouched rat is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies [4,6,13,16,17] have reported that the secretory granules of bronchial serous acini show a marked variation in electron-density. According to Spicer et al [21,22], human and rat airway serous cells are not only characterized by spherical electron-dense SG typical of serous cells, but smaller elongated granules and periodatereactive small bodies of cylindrical shape were also frequently identified. According to lchikawa and lchikawa [9,10], who compared standard and rapid freezing fixation and from the present results, we can suggest that SG2-and SG4-phenotypes are representative of mature stages of the serous granules.…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirms the presence of lysozyme in the submucosal serous cells of the human upper [23,24] and lower [5] respiratory tract and their absence from the submucosal mucous cells. In all the studies mentioned and in reviews on the histochemistry of respiratory epithelium and submucosal glands [21], the morphological heterogeneity of the serous cell secretory granules and irregular distribution of lysozyme within these different granules is reported, although no quantitation of the lysozyme-staining serous cell SG has been carried out. It has already been reported by De Water et al [6] and Puchelle et al [18] that the bronchial antileukoproteinase (also called bronchial inhibitor), a protein which like lysozyme participates in lung defense, is not distributed uniformly in the various SG-phenotypes of the human bronchial glands.…”
Section: Discussionmentioning
confidence: 99%
“…The glands are present predominantly in the intercartilagenous submucosa on the ventral aspect and their density decreases towards the bronchial bifurcation. There is some strain variability in the distribution of glands as Sprague-Dawley and Brown Norway rats have submucosal glands throughout, whereas F344 rats have none in the lower trachea and bronchi (Widdicombe et al, 2001;Ohtsuka et al, 1997;Spicer et al, 1982). The tracheal epithelium is supported by fibrous connective tissue, smooth muscle, and cartilage rings, but the rings disappear soon after the airways enter the lung.…”
Section: Trachea Bronchi and Bronchiolesmentioning
confidence: 99%